A CROSS-SECTIONAL ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICES OF CHRONIC KIDNEY DISEASE IN GENERAL POPULATION OF PAKISTAN (The Research of Medical Science Review, 2024)
This study aimed to assess the knowledge, attitude, and practices (KAP) regarding chronic kidney disease (CKD) among the general population of Lahore, Pakistan. A cross-sectional design was employed, and the study was conducted across five diverse locations in Lahore: Punjab University, corporate offices on Mall Road, Wapda Colony, Samanabad, and Sabzazar. A total of 250 participants, including both males and females aged 18 years and above, were included in the study. The analysis revealed a predominance of male participants (71.6%). The mean scores for knowledge, attitude, and practices were 5.02 ± 1.70, 3.79 ± 1.40, and 5.16 ± 2.00, respectively. Most participants demonstrated inadequate knowledge, negative attitudes, and poor practices regarding CKD. The findings indicate that the levels of knowledge, attitude, and practices related to CKD in the general population of Lahore were unsatisfactory. These results highlight the urgent need for educational seminars and community-based awareness programs to enhance public understanding and improve practices concerning CKD prevention and management.